Desertification and global climate change – Little Ice Age desertification in Iceland? - Helldén, Ulf; Brogaard, Rannveig (International Union of Soil Sciences (IUSS), 1999)
1. INTRODUCTION Geographers at the University of Lund have been active in research on desertification/ land degradation and environmental change monitoring of African drylands since the mid 1970’ies and of Asian drylands since the beginning of the 1990’ies. The results obtained so far do not confirm the concept of desertification as a mainly man made phenomena but indicate that the importance of climate variability and change has been underestimated (Helldén 1991). To learn about the importance of climatic fluctuations versus human impact on land degradation in arctic and sub-arctic environments, Iceland was selected for further studies. Iceland is not an arid, semi-arid or dry sub-humid region. Therefore the land degradation it is suffering cannot be called "desertification" in the strict sense as defined by the UN. On the other hand there is no doubt that land degradation has led to the creation of extensive desert like conditions in many areas of Iceland. In this sense, “desertification” is an Icelandic reality indicating the introduction and spread of desert like conditions in landscapes where there should not be any. 2. RESULTS There are few areas in Europe that have suffered such a severe and extensive land degradation as Iceland, leading to the creation of long lasting desert like conditions. It is estimated that when Iceland was settled, in 874 , at least 60% of the country was vegetated and that forests covered 15-25% of the country’s area (Bergþórsson 1998, Þórarinsson 1961, Einarsson 1963, Þorsteinsson 1973). The vegetative cover is now about 27%. There is almost no forest (The Agricultural Ministry 1986, IGI/LMÍ 1993, Arnalds et al.1997). The scientific and political societies in Iceland often relate the land degradation problems to human over use of the rangelands, starting with the introduction of cattle and sheep rasing at the time of the settlement 874 AD. They consider overgrazing and overuse of the woodlands for fuelwood and charcoal production to be the most important processes opening and ...